Comportamento individual de bovinos Nelore e relações com desempenho em regime de confinamento e reprodução - Soares, Désirée Ribeiro [UNESP] (2015)
In the present thesis we hypothesized that temperament traits can be used as indicators of the individual capacity of cattle to adapt to the feedlot environment, and that pregnant heifers with better temperament can show better results of growth and reproductive performance, since they have greater motivations to compete to access the feed bunk. Thus, the aim of the study on the second chapter was to assess the use of flight speed method (FS, m.s-1) to predict the cattle's ability to adapt to the feedlot environment. Five hundred and forty-nine Nellore bull calves were used in this study, which was carried out over two consecutive years; Year 1 (2012, N = 268) and Year 2 (2013, N = 281). The animals consisted of two groups: i) Group 1 averaging 237.29 ± 22.30 d of age and 280.09 ± 29.05 kg of BW (n = 141) in yr 1, and 276.33 ± 12.24 d of age and 299.26 ± 30.09 kg of BW (n = 143) in yr 2 and; ii) Group 2 averaging 324.57 ± 32.20 d of age and 318.68 ± 36.07 kg of BW (n = 127) in yr 1, and 332.83 ± 24.86d of age and 318.16 ± 47.99 kg of BW (n = 138) in yr 2. During the experimental period, calves from each group were allocated equally into one of two feedlot pens (~ 40 m2.animal), and each pen contained eight adjacent electronic troughs (GrowSafe® System Ltd.) to document individual feeding behavior and intake. Feeding behavior variables assessed included bunk attendance frequency (BAf, visits/d), bunk attendance duration (BAd, min/d), and eating rate (ER, g/min-1; feed intake was assessed by dry matter intake (DMI, kg/d). FS (m.s-1) was measured four times during the trial, on the first day (FS1, immediately before the animals entry in the feedlot facilities), and approximately every 28 days (FS2, FS3, and FS4) after. Based on these measurements, two additional FS variables were calculated for each animal including; the arithmetical means of FS (FSmean) and the differences between FS1 and FS4 (FSdiff). Consequently, FSdiff was ...